Essays on Halakhah in the New Testament - Jackson, Bernard S. (Jewish and Christian perspectives series, 2010)
Historical observations on the relationship between letter and spirit -- The prophet and the law in early Judaism and the New Testament -- The trials of Jesus and Jeremiah -- Testes singulares in early Jewish law and the New Testament -- Susanna and the singular history of singular witnesses -- The Jewish background to the prodigal son : an unresolved problem -- Risk-taking shepherds -- "Holier than thou"? : marriage and divorce in the scrolls, the New Testament and early Rabbinic sources.